Samopomoc jako alternatywny sposób zapewnienia efektywnej ochrony praw prywatnych w prawie rzymskim - Amielańczyk, Krzysztof (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article aims to present Roman regulations concerning self-help, from the perspective of the methods of classifying its legality taking into account both the normative contents of original laws (lex duodecim tabularum, lex Aquilia, ius praetorium), as well as those added by later legislative factors: emperors and jurisprudence. Self-help was an alternative way to secure effective protection of private rights in Roman law since archaic period to Justinian’s time. The active self-help can be differentiated from the passive one. The active self-help have been constantly limited and finally was forbidden by decretum divi Marci. As to the passive self-help one may say, that the presence and meaning of vim vi repellere licet principle in the Roman private law was obvious from its very beginning. Romans did not come up with theory on the self-help, specially with theory of the justification of lawful killing. However, in spite of the absence of proper constructions of self defense in Roman private law, this is out of question that Romans could agree with the rule: “force can be repelled by force”. In this way, under the right to “necessary self-defense” that already stemmed from the very law of nature, yet was confirmed in laws, it was even allowed to kill attacker who threatened to violate such interests of the victim as life, health or property.